Tantangan Pembinaan Keagamaan melalui Media Sosial pada Masyarakat Lereng Merapi di Masa Pandemi COVID 19 - Herawati, Azizah (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2021)
This paper describes the phenomenon of using social media as a means of religious development in the era of the COVID-19 pandemic. The social media access that by Islamic Religious Counselors has not been effective during the COVID-19 period. This paper describes the various obstacles that challenging for Islamic Religious Counselors in carrying out religious development in the Merapi slope community by using social media facilities. We used qualitative approach to collect the data. We did participatory observation, in-depth interviews, discussions and documentation used and then described. The results show that the obstacles encountered in the process of religious development for the Merapi slope community by using social media as a means of religious development during the COVID-19 pandemic are such as limited facilities, lack of ability to access social media and lack of public interest in the media. This situation will be different from other regions with access and supporting facilities, because there are several factors that cause it, such as education, skill and the economy